Synthesis of new alkoxy substituted 4-piperidinobenzylidene malononitrile (PDCST) nonlinear optical chromophores - Vuong, Nguyen Quoc; Nakjoong, Kim; Phuong Thao, Tran Thi; Tuan, Nguyen Le; Sung, Tran Van (Vietnam Journal of Chemistry, 2017)
The new alkoxy-substituted 4-piperidinobenzylidene malononitrile (PDCST) nonlinear optical chromophores were synthesized for investigation into substitutional effect on electrooptic properties and response time. The concise four-step procedure afforded PDCST skeleton with various alkoxy-substituted groups such as methoxy, ethoxy and isobutoxy. Structures were confirmed by H, C-NMR and EI-MS spectroscopic analysis. Keywords. Nonlinear optical chromophores, 4-piperidinobenzylidene malononitrile (PDCST), bromination; formylation; Buchwald-Hartwing, Knoevenagel condensation.